2009
DOI: 10.1103/physreve.80.041128
|View full text |Cite
|
Sign up to set email alerts
|

Understanding totally asymmetric simple-exclusion-process transport on networks: Generic analysis via effective rates and explicit vertices

Abstract: In this paper we rationalize relevant features of totally asymmetric simple-exclusion processes on topologies more complex than a single segment. We present a mean-field framework, exploiting the previously introduced notion of effective rates, which we express in terms of the average particle density on explicitly introduced junction sites. It allows us to construct the phase behavior as well as the current-density characteristic from well-known results for a linear totally asymmetric simple-exclusion-process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
80
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 47 publications
6
80
1
Order By: Relevance
“…Different versions of simple networks were studied in Refs. [4,5]. In the former reference two cases were investigated: (a) two vertices of degree 3, connected by three chains, one of which has the opposite direction to the remaining two (closed system), and (b) two vertices of degree 3, connected by two chains with the same direction; the remaining incoming and outgoing chains are coupled to * nina@imbm.bas.bg † brankov@theor.jinr.ru reservoirs with the same particle density (open counterpart).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different versions of simple networks were studied in Refs. [4,5]. In the former reference two cases were investigated: (a) two vertices of degree 3, connected by three chains, one of which has the opposite direction to the remaining two (closed system), and (b) two vertices of degree 3, connected by two chains with the same direction; the remaining incoming and outgoing chains are coupled to * nina@imbm.bas.bg † brankov@theor.jinr.ru reservoirs with the same particle density (open counterpart).…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [5] graphs containing vertices of degree 4 and out-degrees 1, 2, and 3 were considered. The notion of particle-hole symmetry in the presence of a junction was carefully analyzed and an appropriate interpretation on the microscopic level was given.…”
Section: Introductionmentioning
confidence: 99%
“…These systems allow additional motion of particles in the TASEPs and can be interpreted as networks of TASEPs and reservoirs, where each site in a lattice is connected with the particle reservoir or a site in a different TASEP. On the other hand, the TASEP on networks has been focused on recently [16][17][18][19]. The results have concluded that the dynamics of the system depends on structure of the networks.…”
Section: Introductionmentioning
confidence: 99%
“…Our goal here is to present a study of the effects, arising in TASEP, defined on a simple example of such a network: a linear chain of attachment sites with a double-chain defect inserted in it [25]. For other studies of TASEP on topologies more complex than a single segment see [26,27,28,29]. Recently, applications to biological transport have motivated generalizations of the TASEP to cases when the entry rate is chosen to depend on the number of particles in the reservoir (TASEP with finite resources) [30,31].…”
Section: Introductionmentioning
confidence: 99%